Pentacyclic Triterpenoids, Phytosteroids and Fatty Acid Isolated from the Stem-bark of Cola lateritia K. Schum. (Sterculiaceae) of Cameroon origin; Evaluation of Their Antibacterial Activity - Michael H.K. Kamdem (Elsevier, 2022)
The phytochemical investigation on the chemical constituents of dichloromethane-methanol (1:1) stem-bark extract of Cola lateritia K. Schum. (Sterculiaceae) led to the isolation and characterization of five pentacyclic triterpenoids, one fatty acid and two phytosteroids. The compounds were identified as heptadecanoic acid (1), maslinic acid (2), betulinic acid (3), lupenone (4), lupeol (5), friedelin (6), β-stigmasterol (7) and ß-sitosterol-3-O-ß-D-glucoside (8). Their structures were determined by NMR analysis (1H, 13C, DEPT-135, COSY, HMBC and HSQC), high-resolution mass spectrometry (HR-ESI-MS) and comparisons with published data in the literature. This work, to the best of our knowledge, is the first isolation and identification of these compounds in pure forms from Cola lateritia. Also, compounds 1–3 are reported for the first time from Cola genus. In vitro antibacterial activity of the isolated compounds (1–8) and the crude extract were evaluated against Bacillus subtilis, Staphylococcus epidermidis, Enterococcus faecalis, Mycobacterium smegmatis, Staphylococcus aureus, Enterobacter cloacae, Klebsiella oxytoca, Proteus vulgaris, Klebsiella pneumonia, Escherichia coli, Proteus mirabilis and Klebsiella aerogenes with streptomycin, nalidixic acid and ampicillin as standard antibacterial drugs. Compound 2 was active against E. faecalis (MIC = 18.5 µg/mL), and it was 6.9 and 28 times lower and active than that of streptomycin (MIC 128 µg/mL) and nalidixic acid (MIC > 512 µg/mL) respectively. All the isolated compounds and crude extract showed significant activities against the tested bacterial strains.